Delinquency and its impact on the profitability of the Municipal Savings and Credit Bank of Piura – Peru - Valladolid Braco, Wellington Emmanuel (2022)
The general objective was to determine the impact of delinquency on the profitability of Caja Municipal de Ahorro y Crédito de Piura, 2015-2021. Furthermore, applied research was used, with a non-experimental cross-sectional design and a quantitative approach. The technique used was documentary analysis of the financial statements for the periods 2015 to 2021 of Caja Piura at the national level, and the documentary analysis guide was used as an instrument. The descriptive results revealed that the overdue portfolio, the heavy portfolio and the high-risk portfolio have reduced the profitability of Caja Piura at the national level in the last seven accounting periods (2015 to 2021), with the year that most affected the ROA and ROE in 2020 due to the economic slowdown at the national level. It is concluded that delinquency has a direct and significant impact on the profitability of the Caja Municipal de Ahorro y Crédito de Piura, 2015-2021, given that when delinquency is at a high level, the savings bank makes a loss in its financial statements.